Migration and female genital mutilation - Sandrine Mesplé-Somps (IZA World of Labor, 2016)
More than 100 million women and girls in the world have had their genitals cut for cultural, religious, or other non-medical reasons. Even though international organizations condemn female genital mutilation (FGM), or cutting, as a violation of human rights, and most nations have banned it, it remains prevalent in many African countries, and is slow to decline. This persistence raises questions about the effectiveness of international and national laws prohibiting the practice as well as the potential role of returning migrants in changing embedded cultural norms. Does migration change migrants' opinions and attitudes to this custom? If so, do they transfer the new norms to their origin countries?
Keywords: I15; O55; F22; 330; migration; social norms; female genital mutilation (FGM); Africa